Coalbed Methane - an unconventional - clean energy, the forming, extraction, and potential of Indonesia's Coalbed Methane as future source energy for Indonesia - Lucy Kartikasari; Trisna Suntara (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
Coalbed Methane (CBM) is natural gas produced in coal seams through coalification process. CBM trapped in the pores of coal and mobilization capacity is affected by cracks which are owned by the coal reservoir. Methane is formed by mycobacterial activity (biogenic) or heat (thermogenic) during the coalification process. In use, the emissions that generated from CBM is around 25 tons per GWh. For comparison, the emissions generated by the use of coal exceeding one thousand tons per GWh. From these data, CBM is a cleaner energy source than coal. CBM potential in Indonesia is fourth ranked after the United States, China, and Australia. This potential spread in Central Sumatra, Sekayu, Barito, and Kutai. The total potential of CBM in Indonesia reaches 453 TCF. Thus, the CBM is one of energy source which is potentially provide greater energy intake in welcoming the issue of Indonesia's energy independence in 2025.
Keywords: 650; CBM; energy; Indonesia